Pengaruh Brand Awareness, Brand Image Terhadap Keputusan Pembelian Dengan Minat Beli - Meike, Patrizia; Budi Haryono, PM.; Tecoalu, Melitina (GEMA EKONOMI, 2023)
This study aims to determine the effect of brand awareness and brand image on purchasing decisions with purchase intention as an intervening variable on Marcks loose powder in Jakarta. The method used in this research is a quantitative research method. The population in this study are consumers who buy Marcks loose powder products. The sample size is taken using the Hair Formula. The research sample was determined by purposive sampling technique with a final sample of 100 respondents who were buyers or users of Marcks powder. The data collection technique was carried out using a questionnaire technique with a Likert scale type. The results of the research conducted show that brand awareness and brand image have a positive and significant influence on purchasing decisions, the same thing with brand image has a positive and significant influence on purchase intention, while brand awareness does not have a positive influence on purchase intention. The results of the indirect influence test show that there is a positive and significant influence of brand image on purchasing decisions through purchase intention, and brand awareness does not have a positive and significant effect on purchasing decisions through purchase intention.